Video-based e-learning program for schoolteachers to support children of parents with mental illness: a cluster randomized trial - Masako Kageyama; Atsunori Matsushita; Ayuna Kobayashi; Taku Sakamoto; Yasuhiro Endo; Setsuko Sakae; Keiko Koide; Ryotaro Saita; Hiyuka Kosaka; Satoko Iga; Keiko Yokoyama (BMC, 2023)
Abstract Background Some children of parents with mental illness need support. This study aimed to develop and test the effectiveness of an e-learning program for training elementary schoolteachers to support children of parents with mental illness. Methods The program, which included a 30-min video-based e-learning program, aimed to help schoolteachers gain basic knowledge about mental illness and children of parents with mental illness, recognize children in need of support, and gain confidence in supporting them. A school-based cluster randomized controlled trial was conducted, and the schools were randomly divided into intervention and control groups. The teachers at these schools signed up for the program and participated individually. The outcome measures for the schoolteachers were evaluated at three time points: baseline (T1), post (T2), and one month later (T3). Along with the Sense of Coping Difficulty subscale (primary outcome measure), the following self-developed outcome measures were used: actual behaviors and attitude toward supporting children, knowledge, and self-assessment of program goals achievement. The Sense of Coping Difficulty subscale results at T3 were compared between the groups. Effectiveness over time was assessed for all the outcome measures. The interaction between baseline and intervention effects on the Sense of Coping Difficulty subscale was analyzed. As a part of the process evaluation, open-ended text responses were analyzed qualitatively. Results Baseline responses were collected from 87 participants in the intervention group and 84 in the control group. The total score of the Sense of Coping Difficulty subscale at T3 was significantly lower in the intervention group than in the control group (p = 0.007). Over time, a significant effect was observed on the Sense of Coping Difficulty subscale, actual behavior, knowledge of onset timing and probability of onset, and achievement of all program goals. Exploratory analysis was particularly effective for those who encountered a high level of difficulty in supporting children. The participants' text responses indicated that they planned to look carefully at children's backgrounds and stay close to them in the future. Conclusions The program was effective for schoolteachers in supporting children of parents with mental illness. Trial registration UMIN000045483; 14/09/2021.